Features physical education schoolchildren in view somatotype - Трачук, С. В.; Делбані, Х. (Slobozhanskyi Herald of Science and Sport, 2011)
The questions assess the constitutional status of students in physical education. It also analyzed the data that characterize children of different body types and combinations of specific questions of constitutional signs of a growing organism in the performance of physical exercise, which confirms the need for a differentiated approach in the construction process of physical education students.